2018
DOI: 10.1596/1813-9450-8388
|View full text |Cite
|
Sign up to set email alerts
|

Why Are So Many Water Points in Nigeria Non-Functional? An Empirical Analysis of Contributing Factors

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The functionality of water schemes has a regional dimension, with projects in the southern region more likely to fail than in the north over 15 years; 51 percent of these failures are due to fixed variables such as political region and hydrogeology [84]. Water schemes sustainability is comparatively better in the north in terms of greater water access.…”
Section: Infrastructural and Spatial Divisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functionality of water schemes has a regional dimension, with projects in the southern region more likely to fail than in the north over 15 years; 51 percent of these failures are due to fixed variables such as political region and hydrogeology [84]. Water schemes sustainability is comparatively better in the north in terms of greater water access.…”
Section: Infrastructural and Spatial Divisionsmentioning
confidence: 99%
“…Water project failures are a crucial challenge in Nigeria. For example, in the rural water supply sector, functionality and sustainability as concepts are scrutinised due to the preponderance of failed water projects [84,87,108]. The FMWR observed that 116 projects were still uncompleted or ongoing after an average of 15 years since commencement; 38 irrigation and drainage projects, 37 dam projects, and 41 water supply projects [109].…”
Section: Infrastructure Failures and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The rural water literature has also documented the conditions under which community managed service delivery outcomes are more sustainable. Most studies use correlations to single out variables, or groups of variables, to assess their impact on sustainable community management (Andres et al 2018;Fisher et al 2015;Lockwood and Smits 2011;World Bank 2017a). 6 One set of identified factors (1997) analyzing successful public sector reforms in an otherwise difficult governing condition.…”
Section: The Sustainability Of Rural Water Systems -A Review Of Evidencementioning
confidence: 99%
“…Yet, despite attempts by development practitioners to improve the sustainability of this method of delivery, the evidence remains mixed. Studies have documented the failure of community-led water points 1 as a critical concern in most parts of the world (Andres et al 2018;Borja Vega et al 2017;Fisher et al 2015;World Bank 2017b). Globally, 30 to 40 percent of community-managed water systems are estimated to be malfunctioning much sooner than their infrastructural life.…”
Section: Introductionmentioning
confidence: 99%